Circulation Pattern of Hospital Type B in Emergency. (Case Study: Hospital Sumohardjo Urip) - Suwantoro Suwantoro; Munawaroh A S (International Conference on Engineering and Technology Development (ICETD), 2017)
Hospitals are the type of buildings that have a lot of users to be met needs. All users are doing the movement. In performing this movement, the use of the elements of circulation so that more and more users, the more complex circulation occurs.The purpose of this study is to mengetahuai circulation in Urip Sumoharjo hospital in emergencies.The method used is Qualitative. Data was collected by questionnaires, interviews, observation records, documentation / capturing images, the data of the book, the data from the internet.The research instrument guide frame of reference, Laptop, literature book, camera and internet. Data analysis was performed with data reduction, data presentation and conclusion.The results obtained in this study did not meet the standards yaituerbang entry due to lack of separation of access for pedestrians and vehicles, car parking area visitors are not meeting the standard because there is no protection against the weather. Pedestrian circulation does not meet the standards because of the lack of protection against rain and hot sun for pedestrians from the parking area to the hospital building. Urip Sumoharjo; Directions opening the door did not meet the standard; Emergency door and emergency staircase are not available; and the use of the material for the floor does not meet standards because of slippery